2016
DOI: 10.1111/iwj.12638
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maceration and wound healing on diabetic foot ulcers in Indonesia: a prospective study

Abstract: The aim of this study was to clarify the relationship between maceration and wound healing. A prospective longitudinal design was used in this study. The wound condition determined the type of dressings used and the dressing change frequency. A total of 62 participants with diabetic foot ulcers (70 wounds) were divided into two groups: non-macerated (n = 52) and macerated wounds (n = 18). Each group was evaluated weekly using the Bates-Jensen Wound Assessment Tool, with follow-ups until week 4. The Mann-Whitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
(19 reference statements)
1
23
0
1
Order By: Relevance
“…; Haryanto et al. ; Pemayun et al. ; Purnamasari & Waspadji ) or intradisciplinary teams (Adriono et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Haryanto et al. ; Pemayun et al. ; Purnamasari & Waspadji ) or intradisciplinary teams (Adriono et al.…”
Section: Resultsmentioning
confidence: 99%
“…When searching for papers regarding maceration, the term appears to be ill-defined and usually mentioned only as part of a wider study. However it is clear that maceration is a severe condition that has been shown to cause patients discomfort and pain, 14 as well as prolonging healing time 6 and therefore merits more focused research. There is limited empirical research that is able to inform clinical practice on how to prevent maceration rather than managing the condition once it has already occurred.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to exuding wounds, Haryanto et al 6 demonstrated that if maceration levels were high then wound healing time also increased. However, Koh et al's 7 earlier study found no significant association between wound duration and hydration scores.…”
Section: Introductionmentioning
confidence: 99%
“…Maceration decreases the physical and chemical integrity of the stratum corneum, which acts as a predisposing factor for potential microbial invasion and increased susceptibility to injury by mechanical forces, ultimately leading to enlargement of the wound. Maceration increased susceptibility to mechanical forces and infection [18,19].…”
Section: Macerationmentioning
confidence: 99%